Cumulative lifetime stress exposure and leukocyte telomere length attrition: The unique role of stressor duration and exposure timing. (June 2019) - Mayer, Stefanie E.; Prather, Aric A.; Puterman, Eli; Lin, Jue; Arenander, Justine; Coccia, Michael; Shields, Grant S.; Slavich, George M.; Epel, Elissa S.
Highlights: We examined the effect of lifetime stress exposure on leukocyte telomere length-LTL. Greater count of lifetime stressors predicted greater LTL shortening over 2 years. This was only significant for chronic lifetime and chronic childhood stressors. Results show the unique effects of stressor duration and timing on LTL attrition. Abstract: Background: Stress exposure occurring across the lifespan increases risk for disease, potentially involving telomere length shortening. Stress exposure during childhood and adulthood has been cross-sectionally linked with shorter telomere length. However, few longitudinal studies have examined telomere length attrition over time, and none have investigated how stressor duration (acute life events vs. chronic difficulties), timing (childhood vs. adulthood), and perceived severity may be uniquely related to telomere length shortening. Methods: To address these issues, we administered a standardized instrument for assessing cumulative lifetime stress exposure (Stress and Adversity Inventory; STRAIN) to 175 mothers of children with Autism Spectrum Disorder or neurotypical children and measured their leukocyte telomere length (LTL) at baseline and 2 years later. Results: Greater count of lifetime stressors was associated with shorter LTL at baseline and greater LTL attrition over time. When separating lifetime stressors into acute life events and chronic difficulties, only greater count of chronic difficulties significantly predicted shorter baseline LTL and greater LTL attrition. Similarly, when examining timing of stressor exposure, only greater count of chronic childhood difficulties (age < 18) significantly predicted shorter baseline LTL and greater LTL attrition over the 2-year period in mid-life. Importantly, these results were robust while controlling for stressors occurring during the interim 2-year period. Post-hoc analyses suggested that chronic difficulties occurring during earlier childhood (0–12 years) were associated with greater LTL attrition. Cumulative stressor severity predicted LTL attrition in a parallel manner, but was less consistently associated with baseline LTL. Conclusions: These data are the first to examine the effects of different aspects of cumulative lifetime stress exposure on LTL attrition over time, suggesting that accumulated chronic difficulties during childhood may play a unique role in shaping telomere shortening in midlife.